2021
DOI: 10.3389/fcvm.2021.724254
|View full text |Cite
|
Sign up to set email alerts
|

Schistosome-Associated Pulmonary Arterial Hypertension: A Review Emphasizing Pathogenesis

Abstract: Schistosomiasis, especially due to Schistosoma mansoni, is a well-recognized cause of pulmonary arterial hypertension (PAH). The high prevalence of this helminthiasis makes schistosome-related PAH (Sch-PAH) one of the most common causes of this disorder worldwide. The pathogenic mechanisms underlying Sch-PAH remain largely unknown. Available evidence suggests that schistosome eggs reach the lung via portocaval shunts formed as a consequence of portal hypertension due to hepatosplenic schistosomiasis. Once depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Current therapies for SchPAH rely on nitric oxide pathway inhibitors such as phosphodiesterase type 5 inhibitors (sildenafil and tadalafil), soluble guanylyl cyclase stimulators (riociguat), endothelian receptor antagonists (bosentan, ambrisentan and macitentan) and prostacyclin analogues (epoprostenol, treprostinil, iloprost, and the nonprostanoid IP-receptor agonist selexipag), as fully described by S ibomana et al [ 47 ]. Experience has shown that phosphodiesterase type 5 inhibitors improve symptoms and may also increase survival rates [ 48 ].…”
Section: Pulmonary Schistosomiasismentioning
confidence: 99%
“…Current therapies for SchPAH rely on nitric oxide pathway inhibitors such as phosphodiesterase type 5 inhibitors (sildenafil and tadalafil), soluble guanylyl cyclase stimulators (riociguat), endothelian receptor antagonists (bosentan, ambrisentan and macitentan) and prostacyclin analogues (epoprostenol, treprostinil, iloprost, and the nonprostanoid IP-receptor agonist selexipag), as fully described by S ibomana et al [ 47 ]. Experience has shown that phosphodiesterase type 5 inhibitors improve symptoms and may also increase survival rates [ 48 ].…”
Section: Pulmonary Schistosomiasismentioning
confidence: 99%
“…For instance, some hookworms cause chronic iron-deficiency anemia; and iron deficiency has been reported to be associated with an increase in hsCRP or other inflammatory markers among healthy adults [28,29]. Through egg migration-induced inflammation, egg embolization, and granuloma development, Schistosoma species are causes of cancer, induce renal diseases or pulmonary hypertension which can cause right ventricular failure [30]. Heavy trichuriasis causes chronic infiltration of inflammatory cells in the colon of infected children as well as iron-deficiency anemia [31].…”
Section: Discussionmentioning
confidence: 99%
“…Schistosome‐related PAH (Sch‐PAH) is a fatal complication of chronic schistosomiasis infection with unknown mechanism, and a leading cause of PAH‐related morbidity and mortality worldwide 54,55 . Current evidence suggests that mechanical obstruction of lung vasculature by embolized eggs, systemic inflammation, pulmonary vascular remodeling, and underlying liver disease might be the most relevant pathogenic mechanisms for Sch‐PAH 56 . Female C57/BL6 mice can develop severe vascular remodeling from 12 weeks onwards after transcutaneous injection with a low dose (approximately 30 cercariae) of Schistosoma mansoni , characterized by perivascular inflammation, marked medial thickening and the formation of plexiform‐like lesions without significant PH 57 .…”
Section: Non‐invasive Models In Vivomentioning
confidence: 99%
“…54,55 Current evidence suggests that mechanical obstruction of lung vasculature by embolized eggs, systemic inflammation, pulmonary vascular remodeling, and underlying liver disease might be the most relevant pathogenic mechanisms for Sch-PAH. 56 Female C57/ BL6 mice can develop severe vascular remodeling from 12 weeks onwards after transcutaneous injection with a low dose (approximately 30 cercariae) of Schistosoma mansoni, characterized by perivascular inflammation, marked medial thickening and the formation of plexiform-like lesions without significant PH. 57 Female mice manifested a heavier worm burden than males during chronic infection, as the presence of testosterone results in decreased schistosome survival and increased host survival in experimental infections, and the extent of pulmonary vascular remodeling correlated with levels of inflammatory cytokines and lung egg burden.…”
Section: Schistosome-related Pahmentioning
confidence: 99%